2018
DOI: 10.1161/circheartfailure.118.005082
|View full text |Cite|
|
Sign up to set email alerts
|

Omega-3 Therapy Is Associated With Reduced Gastrointestinal Bleeding in Patients With Continuous-Flow Left Ventricular Assist Device

Abstract: BACKGROUND: Gastrointestinal bleeding (GIB) is a common complication seen in patients supported with left ventricular assist devices (LVADs) and is related to increased inflammation and angiogenesis. Omega-3 is an unsaturated fatty acid that possesses anti-inflammatory and antiangiogenic properties. This study aims to assess the prophylactic efficacy of treatment with omega-3 on the incidence of GIB in LVAD patients. METHODS AND RESULTS: Among consecutive 166 LVAD patients enrolled in this analysis, 30 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Our team recently demonstrated that omega-3, one of the unsaturated fatty acids, had a protective effect of gastrointestinal bleeding in LVAD patients. The mechanism likely relates to the suppression of angiopoietin-2 that is located upstream of the angiogenetic signal cascade [13]. However, we could not obtain any dietary data in this study.…”
Section: Less Bleeding In J-macsmentioning
confidence: 74%
“…Our team recently demonstrated that omega-3, one of the unsaturated fatty acids, had a protective effect of gastrointestinal bleeding in LVAD patients. The mechanism likely relates to the suppression of angiopoietin-2 that is located upstream of the angiogenetic signal cascade [13]. However, we could not obtain any dietary data in this study.…”
Section: Less Bleeding In J-macsmentioning
confidence: 74%
“…In combination, these observations describe the multifactorial competing mechanisms that create the considerable challenge of managing the balance between nonsurgical bleeding and thrombotic events in CF-LVAD recipients. Improving our understanding of the nuances associated with the physiologic pathways and mechanisms of action that link vWF, pulsatility, and pump shear to clotting disorders, as well as likely contributors to angiodysplasia such as low-molecular-weight vWF multimers 17 and reduced omega-3 fatty acid intake, 18 will help advance the efforts to promote the clinical optimization of CF-LVAD therapies. To provide further information regarding the potential interaction between reduced arterial pulsatility and pump shear, studies looking specifically at vWF or GIB in patients with heart failure implanted with a mechanical circulatory support system were included: LVAD pumps: HeartMate II (Abbott, Chicago, Ill); HeartMate3, HeartWare HVAD (HeartWare Inc, Framingham, Mass), EVAHEART (EVAHEART Inc, Houston, Tex); and 2 total artificial heart devices: CardioWest (SynCardia Systems, Tucson, Ariz) and CARMAT (V elizy-Villacoublay, France).…”
Section: Von Willebrand Factor Nitric Oxide and Continuous-flow Lefmentioning
confidence: 99%
“…There are anecdotes about the use of octreotide to control bleeding from arteriovenous malformations, but results are contradictory, and again this should be reserved for patients for whom there are no other options to control bleeding . There are preliminary promising data for omega‐3 fatty acids, where the use of 4 g daily resulted in lower rates of GI bleeding (3%) compared to 22% in a retrospective control group, but these results need to be confirmed in a randomized clinical trial …”
Section: Management Strategiesmentioning
confidence: 99%